Study of functionalism in the art of Reog Singo Budoyo - Putri Dyah Indriyani; Rusmaniah; Dedy Ary Nugroho; Sherlu Nur Hikmah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Reyog Singo Budoyo in this study of functionalism provides a point of view that art can grow and develop due to the needs of the surrounding community. This art has many functions and uses that make its existence continue to be maintained. Through these problems, this research was conducted using a qualitative descriptive research method. The object of this research is Reyog Singo Budoyo in the study of the function of symbols, education, social, politics, and aesthetics.